2008
DOI: 10.1038/bmt.2008.395
|View full text |Cite
|
Sign up to set email alerts
|

Granzymes A and B serum levels in allo-SCT

Abstract: Activated cytotoxic T lymphocytes and natural killer cells, which are involved in the pathogenesis of GVHD and viral infections after SCT produce granzymes (Grs). This study performed an ELISA in the serum of 86 patients at various time points before and after Allo-SCT to investigate GrA and GrB levels as potential markers for these serious complications. The increase in Gr levels from the day of transplantation until the appearance of the complication was highly predictive. If GrA increased to three times its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In human HCT patients, granzymes have been used as biomarkers of aGVHD and a predictor of disease severity. In an 86-patient cohort, Kircher et al (52) demonstrated that serum GrA was detected at higher levels than GrB and was a better predictor of disease severity than HLA mismatch or donor/ recipient age. Earlier studies by this same group indicated that GrA, but not GrB, produced in mixed lymphocyte reactions between donor and host PBMCs significantly correlated with GVHD grade posttransplant.…”
Section: Discussionmentioning
confidence: 99%
“…In human HCT patients, granzymes have been used as biomarkers of aGVHD and a predictor of disease severity. In an 86-patient cohort, Kircher et al (52) demonstrated that serum GrA was detected at higher levels than GrB and was a better predictor of disease severity than HLA mismatch or donor/ recipient age. Earlier studies by this same group indicated that GrA, but not GrB, produced in mixed lymphocyte reactions between donor and host PBMCs significantly correlated with GVHD grade posttransplant.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigators from the University of Michigan spearheaded an effort to evaluate the prognostic value of a panel of biomarkers comprised of TNFR1, IL-2Ra, IL-8, HGF, elafin and reg3a. Samples T-cell growth factor, stimulates production of TNF-a and IFN-g Activated NK cells, induces IFN-g production Nakamura et al 16 Fujimori et al 17 Shaiegan et al 18 Mohty et al Visentainer et al 12 Visentainer et al 12 Liem et al 13 Other circulating molecules Uguccioni et al 20 Okamoto et al 21 Luft et al 22 Seidel et al 23 Kircher et al 24 Hubel et al 26 Chen et al 25 Lymphocytetrafficking molecules a4b7 integrin…”
Section: Moving Toward Risk-adapted Approachesmentioning
confidence: 99%
“…23 Granzymes A and B are products of cytotoxic T cells and natural killer cells, and serum levels appeared to parallel the incidence and severity of acute GVHD, although there was an association with CMV infection as well. 24 CD30, a member of the TNFR superfamily, is expressed on the surface of certain activated T cells. Recent studies have shown that CD30 expression appears to be higher on memory T cells in patients with acute GVHD, 25 and soluble CD30 levels have been shown to be increased in the setting of GVHD, 26 possibly revealing a novel target for therapeutic intervention.…”
Section: Il-2mentioning
confidence: 99%
“…41,42 Increased gene expression of granzyme B was detected in patients with aGVHD 43 and an elevated serum level of granzyme B post-HSCT was highly predictive of the risk and severity of aGVHD. 44 However, inter-individual variability in the baseline expression and activity of granzyme B may result from variations in the granzyme B gene. Espinoza et al reported that donors and/or patients with the granzyme B +55 G-allele positive genotype were associated with improved overall survival after unrelated HLA-fully matched T-cell-replete bone marrow transplantation, but failed to find any significant association with aGVHD.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%